Effectiveness assessment of the medical-social rehabilitation of adolescents with mild mental retardation - V. V. Chuhunov; V. L. Pidlubnyi; S. O. Chabaniuk (Zaporožskij Medicinskij Žurnal)
Issues of treatment and rehabilitation of adolescents with mental retardation, improvement of old and new therapies using an integrated approach to rehabilitation, which allows increasing social activity of adolescents with mild mental retardation and improving their quality of life, are remaining relevant and needing further study.